Trajectories of Frailty in the 5 Years Prior to Death Among U.S. Veterans Born 1927–1934. (9th July 2021) - Ward, Rachel E; Orkaby, Ariela R; Dumontier, Clark; Charest, Brian; Hawley, Chelsea E; Yaksic, Enzo; Quach, Lien; Kim, Dae H; Gagnon, David R; Gaziano, J Michael; Cho, Kelly; Djousse, Luc; et al.
Abstract: Background: Electronic frailty indices (eFIs) are increasingly used to identify patients at risk for morbidity and mortality. Whether eFIs capture the spectrum of frailty change, including decline, stability, and improvement, is unknown. Methods: In a nationwide retrospective birth cohort of U.S. Veterans, a validated eFI, including 31 health deficits, was calculated annually using medical record and insurance claims data (2002–2012). K -means clustering was used to assign patients into frailty trajectories measured 5 years prior to death. Results: There were 214 250 veterans born between 1927 and 1934 (mean [ SD ] age at death = 79.4 [2.8] years, 99.2% male, 90.3% White) with an annual eFI in the 5 years before death. Nine frailty trajectories were identified. Those starting at nonfrail or prefrail had 2 stable trajectories (nonfrail to prefrail, n = 29 786 and stable prefrail, n = 28 499) and 2 rapidly increasing trajectories (prefrail to moderately frail, n = 28 244 and prefrail to severely frail, n = 22 596). Those who were mildly frail at baseline included 1 gradually increasing trajectory (mildly to moderately frail, n = 33 806) and 1 rapidly increasing trajectory (mildly to severely frail, n = 15 253). Trajectories that started at moderately or severely frail included 2 gradually increasing trajectories (moderately to severely frail, n = 27 662 and progressing severely frail, n = 14 478) and 1 recovering trajectory (moderately frail to mildly frail, n = 13 926). Conclusions: Nine frailty trajectories, including 1 recovering trajectory, were identified in this cohort of older U.S. Veterans. Future work is needed to understand whether prevention and treatment strategies can improve frailty trajectories and contribute to compression of morbidity toward the end of life.